2013
DOI: 10.1002/chem.201204467
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the Deprotonation Reaction of Alkyl Benzyl Ethers with n‐Butyllithium

Abstract: Kinetic study of the α-lithiation of benzyl methyl ether (BME) by nBuLi has revealed that increasing the concentration of the organolithium compound does not necessarily increase the reactivity, and this is a consequence of the reactivities of the different nBuLi aggregates present in solution. We propose a dimer-based mechanism, in which a pre-complexation step is a key process for substrates bearing a donor oxygen atom that can interact with the lithium cation to form mixed dimers. For these studies, we have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…To reduce the irreversible reaction, a -V 2 O 5 was treated with n -BuLi, which is a strong base that reacts with acidic surface hydroxyl groups. , An expectation here is the decrease of H 2 evolution due to the removal of surface hydroxyl groups. Figure a shows the FT-IR spectra for two a -V 2 O 5 samples.…”
Section: Resultsmentioning
confidence: 99%
“…To reduce the irreversible reaction, a -V 2 O 5 was treated with n -BuLi, which is a strong base that reacts with acidic surface hydroxyl groups. , An expectation here is the decrease of H 2 evolution due to the removal of surface hydroxyl groups. Figure a shows the FT-IR spectra for two a -V 2 O 5 samples.…”
Section: Resultsmentioning
confidence: 99%
“…Because reactivity is strongly dependent on n- BuLi aggregation, the lithiation of benzyl ether 1 follows a pathway in which n -BuLi tetramer–dimer deaggregation occurs in a fast equilibrium step, followed by dimer complexation to the oxygen atom of the ether, and a subsequent proton transfer as the rate-determining step . When the same mechanistic scheme is applied to the lithiation of ester 2 , a rate equation is obtained, k obs = K 1 k 2 [dimer] ( K 1 and k 2 being the precomplexation equilibrium and proton transfer rate constants respectively), which predicts a linear dependence between the observed rate constant and [dimer] (see Figure , right).…”
mentioning
confidence: 95%
“…Our studies on the lithiation of benzyl methyl ether ( 1 ) (Figure ) with n -BuLi in THF/hexane at −80 °C showed that a precoordination step between base and acid occurs prior to the rate-determining proton transfer reaction. We now describe the results of a study on the lithiation of benzyl ester 2 and carbamate 3 , substrates analogous to ether 1 in which the O -substituents show enhanced donor ability.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…13 Similarly, Garcia-Rio et al have identified, by kinetics and NMR measurements, a dimer of n-BuLi solvated by 3 THF and on which the substrate of a deprotonation docks before the reaction starts. 14 The situation is also very clear for LDA, the disolvated dimer (LDA) 2 -2THF of which has been depicted in solution. 15 The electrophile we have retained is propanal, viz.…”
mentioning
confidence: 98%